Diabetic Kidney Disease in FVB/NJ Akita Mice: Temporal Pattern of Kidney Injury and Urinary Nephrin Excretion - Chang, Jae-Hyung; Paik, Seung-Yeol; Mao, Lan; Eisner, William; Flannery, Patrick J.; Wang, Liming; Tang, Yuping; Mattocks, Natalie; Hadjadj, Samy; Goujon, Jean-Michel; Ruiz, Phillip; Gurley, Susan B.; et al. (PLOS ONE, 2012)
Akita mice are a genetic model of type 1 diabetes. In the present studies, we investigated the phenotype of Akita mice on the FVB/NJ background and examined urinary nephrin excretion as a marker of kidney injury. Male Akita mice were compared with non-diabetic controls for functional and structural characteristics of renal and cardiac disease. Podocyte number and apoptosis as well as urinary nephrin excretion were determined in both groups. Male FVB/NJ Akita mice developed sustained hyperglycemia and albuminuria by 4 and 8 weeks of age, respectively. These abnormalities were accompanied by a significant increase in systolic blood pressure in 10-week old Akita mice, which was associated with functional, structural and molecular characteristics of cardiac hypertrophy. By 20 weeks of age, Akita mice developed a 10-fold increase in albuminuria, renal and glomerular hypertrophy and a decrease in the number of podocytes. Mild-to-moderate glomerular mesangial expansion was observed in Akita mice at 30 weeks of age. In 4-week old Akita mice, the onset of hyperglycemia was accompanied by increased podocyte apoptosis and enhanced excretion of nephrin in urine before the development of albuminuria. Urinary nephrin excretion was also significantly increased in albuminuric Akita mice at 16 and 20 weeks of age and correlated with the albumin excretion rate. These data suggest that: 1. FVB/NJ Akita mice have phenotypic characteristics that may be useful for studying the mechanisms of kidney and cardiac injury in diabetes, and 2. Enhanced urinary nephrin excretion is associated with kidney injury in FVB/NJ Akita mice and is detectable early in the disease process.